2006
DOI: 10.1093/ps/85.12.2278
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Campylobacter jejuni from Broiler Carcasses and Slaughterhouse Environment by Amplified Fragment Length Polymorphism

Abstract: We examined the occurrence and diversity of Campylobacter jejuni on broiler carcasses during slaughter of an infected flock and in the slaughterhouse environment during slaughter and postdisinfection before a new production run. During the slaughter of a known C. jejuni infected broiler flock, samples were taken from broiler carcasses at 7 different stages during the process. Thirty-seven sites in the slaughterhouse environment were sampled both during process and postdisinfection. The samples were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…This can be explained by cross contamination from positive batches to negative batches during slaughter and associated carcass preparation (Johannessen et al 2007;Jørgensen et al 2002) through contamination of the slaughterhouse environment (Johnsen et al 2006). Differences between the prevalence of Campylobactercolonised broiler batches and of Campylobacter-contaminated broiler carcasses and possible explanations will be explored further in the Part B report.…”
Section: Prevalence Of Campylobacter-contaminated Broiler Carcassesmentioning
confidence: 99%
“…This can be explained by cross contamination from positive batches to negative batches during slaughter and associated carcass preparation (Johannessen et al 2007;Jørgensen et al 2002) through contamination of the slaughterhouse environment (Johnsen et al 2006). Differences between the prevalence of Campylobactercolonised broiler batches and of Campylobacter-contaminated broiler carcasses and possible explanations will be explored further in the Part B report.…”
Section: Prevalence Of Campylobacter-contaminated Broiler Carcassesmentioning
confidence: 99%
“…To ensure that all possible relevant articles were captured, the search strategy was verified by checking the reference lists of the 3 most recent and relevant primary REVIEW articles (Johnsen et al, 2006;Northcutt et al, 2006;Corry et al, 2007) and a random selection of 3 literature reviews (Yang et al, 2002;Oyarzabal, 2005;Hilmarsson et al, 2006). A few 2007 articles were captured in the search because, as of the date of the search, they were available online and indexed in the database before they were actually published.…”
Section: Literature Searchmentioning
confidence: 99%
“…It is known that some STs are found at a significantly lower frequency on chicken after slaughter compared to the levels in live chickens (Newell et al 2001;Johnsen et al 2006). In this study, STs 418 and 4227 were only found on crates before washing and other STs dominated at later processing stages.…”
Section: Discussionmentioning
confidence: 49%
“…The widespread occurrence of Campylobacter jejuni and Campylobacter coli in the digestive tract of farmed chickens and the automated methods used to slaughter and present these birds to retail outlets help to explain the contribution of poultry meat as a source of human campylobacteriosis. Poultryprocessing plants have also been implicated as a source of contamination as flocks that are free of Campylobacter at slaughter may produce Campylobacter-positive meat after processing (Johnsen et al 2006). The crates used to transport live birds from farms to processing have been shown to harbour Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%